2010
DOI: 10.1007/s10682-010-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal defense in plants: assessment of resource allocation costs

Abstract: Genetic and environmental variation of functional traits within populations might be maintained by natural selection when resource allocation costs (RACs) balance trait benefits. Despite the intuitive appeal of optimization models, empirical tests have failed to support the importance of RACs for plant traits that confer resistance against pests. To address this discrepancy, we modified an early model by allowing the cost function to vary across a resource gradient as predicted for RACs and by assuming that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…We applied two nutrient treatments once weekly as a mixture of water-soluble Peters Professional General Purpose Fertilizer 20N-10P-20K (Scott's Co., Marysville, OH, USA) at 110 ppm N (1×; 1 ppm = 1 mg/L), and 1100 ppm (10×). We selected fertilizer concentrations to be stressful vs. moderate (low vs. medium) based on previous studies of nutrient stress in B. stricta (Siemens et al, 2010(Siemens et al, , 2012. We applied high nutrient levels early in life history to simulate nutrient pulses that occur at snowmelt when seedlings first emerge (Groffman et al, 2001(Groffman et al, , 2011Gavazov et al, 2017) and to enhance seedling establishment (Villar-Salvador et al, 2012;Gan et al, 2015).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied two nutrient treatments once weekly as a mixture of water-soluble Peters Professional General Purpose Fertilizer 20N-10P-20K (Scott's Co., Marysville, OH, USA) at 110 ppm N (1×; 1 ppm = 1 mg/L), and 1100 ppm (10×). We selected fertilizer concentrations to be stressful vs. moderate (low vs. medium) based on previous studies of nutrient stress in B. stricta (Siemens et al, 2010(Siemens et al, , 2012. We applied high nutrient levels early in life history to simulate nutrient pulses that occur at snowmelt when seedlings first emerge (Groffman et al, 2001(Groffman et al, , 2011Gavazov et al, 2017) and to enhance seedling establishment (Villar-Salvador et al, 2012;Gan et al, 2015).…”
Section: Experimental Designmentioning
confidence: 99%
“…Alternatively, individuals can vary in their capacity to acquire resources, such that some individuals have more resources to allocate to multiple functions, which would generate positive relationships between fitness components like growth and survival (Van Noordwijk and de Jong, ; Zera and Harshman, ). Trade‐offs have emerged in response to altered conditions associated with climate change, such as new soil moisture levels (Rosenzweig and Hillel, ; Sheffield and Wood, ) and nutrient availability (Kuzyakov, ; Siemens et al., ). Drought stress has altered both the sign and magnitude of phenotypic and genetic correlations associated with fitness in barley ( Hordeum vulgare ; Shakhatreh et al., ).…”
mentioning
confidence: 99%
“…Several studies have examined these questions in Boechera . Siemens et al. (2010) identified a significant cost of defence when resistant plants were grown in the absence of herbivores.…”
Section: Interactions With Herbivores and Pathogensmentioning
confidence: 99%
“…Several studies have examined these questions in Boechera. Siemens et al (2010) identified a significant cost of defence when resistant plants were grown in the absence of herbivores. This cost of defence was independent of resource availability, and glucosinolate chemical defences did not vary across a resource gradient.…”
Section: Interactions With Herbivores and Pathogensmentioning
confidence: 99%
“…This population genetic differentiation and variation also include the high and low elevation range margin populations studied here (Siemens & Haugen, ). There is also significant quantitative genetic variation for the relevant traits (resistance to herbivores, GS content, abiotic stress‐tolerance) in low elevation range margin populations of B. stricta (Siemens et al, ; Siemens, Keck, & Ziegenbein, ).…”
Section: Discussionmentioning
confidence: 99%